Innocent Victim? The Legend of lady Jane Grey in Nineteenth-Century Historiography and Literature - Walczyk, Katarzyna (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
Although there is a relatively rich bibliography on the Tudor period, much less has been written about Jane Grey, the oldest granddaughter of Mary Tudor (the youngest sister of Henry VIII). The purpose of this research is to present the legend of lady Jane Grey which was created by British historians and dramatists during the nineteenth century and to confront it with the sources from the 16th century. This paper analyzes chronicles, state documents, biographies, histories of England, poems, tragedies and novels from 16th to 19th centuries, which describes the life and reign of Jane Grey. The data are collected mostly from British History Online and Internet Archive. An obtained information can tell researchers a lot about the beginnings of the legend of Jane Grey and its changes, which were created in the following centuries.